Mathematical Model of Foot and Mouth Disease Considering Vaccination Disinfection And Early Quarantine - Wahyudin Nur; Darmawati Darmawati; Nur Afni; Sriwana Bulawan; Nur Haeni; Abdullah Abdullah; Nirma Nirma; Muhammad Aspar; Salim Salim (Leibniz: Jurnal Matematika, 2023)
Foot and Mouth Disease (FMD) is a highly contagious disease that can infect all cloven hoofed animals. FMD is one of the most important infectious viral diseases in the world. This disease is responsible for international losses in livestock production and trade. In this article, we formulate a mathematical model for the spread of FMD in goat farms that considers early quarantine, vaccination, and disinfection interventions. The model constructed is expressed as a system of ordinary differential equations consisting of eight state variables. We determine the basic reproduction number using the next-generation matrix method. Our numerical simulation results show that vaccination has a very crucial role in controlling the spread of FMD and reducing the basic reproduction number. In addition, quarantine interventions for latent and infectious goats are also effective in controlling the spread of FMD. The basic reproduction number can also be suppressed by disinfection and quarantine interventions. Therefore, we recommend implementing routine vaccination, screening and disinfection programs. In addition, farmer should be given education so that they have the ability to identify goats exposed to FMDV so that quarantine can be carried out early.